Automated image processing system design for engineering education: The case of automatic inspection for printed circuit boards - (:unkn) unknown (American Society for Engineering Education, 2015)
An experimental test-bed in engineering education enhances the quality of studies and provides industrial experiences to engineer candidates. The purpose of this paper is to develop a multi-purpose test-bed for detecting defects (faults) on printed circuit boards (PCBs). Specifically, the test-bed utilizes the techniques from image processing. To achieve this aim, first a visual pattern inspection system was designed for PCBs, and second an algorithm was developed for detecting the defects related to PCB traces. The system addresses four main aspects: (i) the automatic inspection; (ii) independent angle of rotation; (iii) displaying the PCB defect area; and (iv) creating a database for defect history. Based on the results derived from several defect tests, our findings show that the system can be adapted with ease for basic industrial applications as well as a training test-bed for engineering courses such as digital image processing. © 2015 American Society for Engineering Education. All rights reserved.